Melting Time, Total Solids, Vitamin C, Hedonic Quality Test of Color, Aroma, Sweet Taste and Overall Soursop Velva (Annona muricata L.) with Various Levels of Carrageenan Concentration - Sayyidah Ghaisani Putri; Yoyok Budi Pramono; Antonius Hintono (Journal of Applied Food Technology, 2021)
This study aims to determine the effect of variations in the concentration of carrageenan on melting time, total solids, vitamin C and hedonic quality test of soursop velva. The materials used in this study were soursop, mineral water, carrageenan, sugar and citric acid. Carrageenan was added in different concentrations, i.e., 0%, 0.25%, 0.50%, 0.75% and 1% (w/w). Further, quality attributes of soursop velva were evaluated, including its melting time, total solids, vitamin C and hedonic quality test. Melting time was measured using a stopwatch, total solids were analyzed using an oven, vitamin C was analyzed using spectrophotometry UV-VIS and hedonic quality test was performed by panelists. The measurement showed a significant difference (P<0.05) in total solids, hedonic quality of color, aroma and overall soursop velva as a result of different carrageenan concentrations. However, the melting time and sweet taste of soursop velva did not show significant differences (P>0.05). The most optimal use of carrageenan concentration in soursop velva is 0.25% because it has a soft texture, long melting time and is most preferred.